Papery solar cells based on dielectric/metal hybrid transparent cathode - Fei Wang; Chen, Zhijian; Xiao, Lixin; Qu, Bo; Qihuang Gong (SOLAR ENERGY MATERIALS AND SOLAR CELLS, 2010)
Poly(3-hexylthiophene) (P3HT):1-(3-methoxycarbonyl)-propyl-1-Phenyl-(6,6)C-61 (PCBM) photovoltaic devices based on ordinary paper as substrate were fabricated. Au layer deposited on paper by RF magnetron sputtering was used as anode. The hybrid layer of LiF co-evaporated with Al was used for transparent cathode, and the light transmittance could reach to similar to 70%. By optimizing the mass proportion of LiF and Al, we could get the best papery solar cells with the short current density and open circuit voltage 0.1 mA/cm(2) and 0.39 V. respectively. The corresponding power conversion efficiency was measured to be 0.13 parts per thousand illuminated with 100 mW/cm(2) air mass 1.5 global (AM 1.5 G) simulated sunlight. (C) 2010 Elsevier B.V. All rights reserved.